IMPLEMENTATION OF THE „BUSINESS ADVISOR“ INFORMATION SYSTEM FOR OPTIMIZING THE ECONOMIC RELATIONSHIPS BETWEEN SUBJECTS IN WOOD CUTTING ACTIVITY (Innovation in Woodworking Industry and Engineering design, 2026)
The sustainable develpoment of forestry is closely related to the rational distribution of the income obtained from the wood use, the main part of it being cutting. For the successful and foresight regulation of the relationships between economic subjects that maintain and perform cutting activity both reliable legal base and intime operarational information are required. Current investigation aims to support the right management decision making by implementing the “Business advisor” information system for the precise definition of the production expenses when determining the initial prices in auction procedures for cutting assignment in the state forests.